SiC-based sandwich material for Flow Channel Inserts in DCLL blankets: Manufacturing, characterization, corrosion tests - Soto, Carlota; García-Rosales, Carmen; Echeberria, Jon; Martínez-Esnaola, José M.; Hernández, Teresa; Malo, Marta; Plataci, Ernests; Muktepavela, Faina (Elsevier Ltd, 2017)
Flow Channel Inserts (FCIs) are key elements in a DCLL blanket concept for DEMO, since they provide the required thermal insulation between the He cooled structural steel and the hot liquid PbLi flowing at ≈700 °C, and the necessary electrical insulation to minimize MHD effects. In this work a SiC-based sandwich material is proposed for FCIs, consisting of a porous SiC core covered by a dense CVD-SiC layer. A method to produce the porous SiC core is presented, based on combining a starting mixture of SiC powder with a spherical carbonaceous sacrificial phase, which is removed after sintering by oxidation, in such a way that a microstructure of spherical pores is achieved. Following this technique, a porous SiC material with low thermal and electrical conductivities, but enough mechanical strength was produced. Samples were covered by a 200 μm thick CVD-SiC coating to form a SiC-sandwich material. Finally, corrosion tests under static PbLi were performed, showing that such a dense layer offers a reliable protection against static PbLi corrosion.
This work has been carried out within the framework of the EUROfusion Consortium and has received funding from the Euratom research and training programme 2014–2018 under grant agreement No 633053. The views and opinions expressed herein do not necessarily reflect those of the European Commission.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Corrosion by PbLi; CVD-SiC coating; DCLL blanket; FCI; Flexural strength; Porous SiC; Thermal conductivity